Efektivitas Penggunaan Aplikasi Marbel dalam Meningkatkan Minat dan Motivasi Belajar pada Siswa Sekolah Dasar - Nadia Nur Nisrina; Arinda Nurmeita Kurniawan; Imam Khoiru Zadi; Aang Kunaepi (IQRO: Journal of Islamic Education, 2023)
This study discusses the effectiveness of marble applications in improving reading ability starting with pronouncing vowels in children who have difficulty reading or lack interest in reading. The ability to recognize letters is the first step for children to have the ability to read and write. In this modern era, letter recognition using educational games on gadgets is still lacking, children use gadgets more just to watch and play. This research aims to increase children's interest and motivation in reading and writing activities by using gadgets as a means to play in the Marbel application. In this study the researcher used the literature study method in which the researcher read and recorded and processed several journals, books, and documents (both printed and electronic) as well as other sources of information data that were considered relevant to the research or study. In order to get valid and relevant data that will attract readers' interest and motivation in terms of educating and developing children's enthusiasm for reading using the Marbel application which contains interesting features so that children do not get bored reading, the features displayed are in the form of interesting games.